Job Satisfaction Mediates Work Environment and Stress on Nurses’ Organizational Commitment: A Study at ABC Hospital, Bali - Muliyanto, Evelyn Christina; Bernarto, Innocentius (GoAcademica Research & Publishing, 2025)
ABC Hospital in Bali is grappling with significant issues concerning its nurses' organizational commitment, evidenced by high turnover rates and clear signs of job dissatisfaction. A preliminary survey underscored this challenge, revealing that over half of nurses (55%) would consider leaving for better opportunities, while a substantial portion (45%) were hesitant to assist colleagues if it encroached on their breaks. This situation poses a direct threat to the quality of the hospital's frontline healthcare services. This study sought to understand how the work environment and work stress influence organizational commitment, specifically examining the mediating role of job satisfaction. Data was gathered from 98 nurses via an online questionnaire and analyzed using SmartPLS 4.0. The findings were conclusive: a positive work environment significantly enhances organizational commitment, while work stress demonstrably diminishes it. The research also confirmed that job satisfaction positively impacts organizational commitment. Looking deeper, the work environment was found to positively influence job satisfaction, and conversely, work stress negatively affected job satisfaction. Crucially, the study established that job satisfaction fully mediates the relationship between both the work environment and work stress, and nurses' organizational commitment. These results strongly suggest that enhancing the work environment quality and effectively managing work stress are vital steps that can lead to improved job satisfaction, ultimately bolstering nurses' organizational commitment. Practically, ABC Hospital should focus on creating a conducive work environment and implementing effective stress management programs to curb turnover and elevate overall nurse performance.